Historia y derecho en la investigación sobre las monarquías ibéricas - Darío G. Barriera; Guillaume Gaudin; Pilar Ponce Leiva (Les Cahiers de Framespa)
This interview with the Argentine historian Darío G. Barriera aims to review the historiographical framework in which the political history of the Catholic Monarchy has developed since the 1990s in the context of Spanish America. The main elements of said framework are the links developed between history and history of law with the idea of jurisdictional power as well as the adaptability of norms and their flexible uses by actors versed in casuistry. This interview provides an opportunity to review the most notable historians and works that have marked Darío G. Barriera between Europe and the Americas.